2005
DOI: 10.1002/dys.298
|View full text |Cite
|
Sign up to set email alerts
|

Measurement error: implications for diagnosis and discrepancy models of developmental dyslexia

Abstract: The diagnosis of developmental dyslexia (DD) is reliant on a discrepancy between intellectual functioning and reading achievement. Discrepancy-based formulae have frequently been employed to establish the significance of the difference between 'intelligence' and 'actual' reading achievement. These formulae, however, often fail to take into consideration test reliability and the error associated with a single test score. This paper provides an illustration of the potential effects that test reliability and meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 71 publications
1
25
0
Order By: Relevance
“…Researchers have disagreed about whether this has theoretical consequences for the relationship between reading/writing skills and other abilities, or whether it is simply a consequence of the notoriously low correlations one is bound to find for difference scores of highly correlated variables (e.g. [63]). Our data leave little doubt that, as a group, dyslexics entering higher education show exactly the profile predicted by the traditional definition of dyslexia, even though at an individual level the difference scores may show large variability.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have disagreed about whether this has theoretical consequences for the relationship between reading/writing skills and other abilities, or whether it is simply a consequence of the notoriously low correlations one is bound to find for difference scores of highly correlated variables (e.g. [63]). Our data leave little doubt that, as a group, dyslexics entering higher education show exactly the profile predicted by the traditional definition of dyslexia, even though at an individual level the difference scores may show large variability.…”
Section: Discussionmentioning
confidence: 99%
“…A discrepancy of ≥20 points occurred among 5% ( p > 0.01) of the norm sample (Elliot, ). Discrepancy analysis is contentious (BPS (British Psychological Society), ), but widespread (Cotton, Crewther, & Crewther, ). Diagnostic thresholds are also subjective, but an occurrence rate of less than 5% of the norm sample is typical (Kavale & Flanagan, ; Meyer, ).…”
Section: Methodsmentioning
confidence: 99%
“…While the discrepancy model can be challenged on the grounds that it introduces measurement error [2], its use has been primarily discredited because supposed differences between high and low IQ poor readers have not proven to be meaningful in educational terms. More recently, findings from neurophysiological studies have indicated no support for the argument that there are different aetiologies for IQ discrepant and nondiscrepant groups in relation to phonological awareness, a very influential aspect of reading disability [3,4].…”
Section: The Resilience Of Discrepancy Testingmentioning
confidence: 99%